Aktualne problemy struktury i działalności banków w Szwecji - Kośmicki, Eugeniusz (Wydział Prawa i Administracji UAM, 1974)
Sweden is the reach est European country. Its developed economy has been influenced to a great extent by the banks what may be subject of a case study. In Sweden, similarly to many other countries there exists a central bank whose activity essentially differs in comparison to the banks of that sort in other countries. It has been a state bank at the beginning of its existence. The commercial banks in Sweden characterize themselves by an advanced concentration. Among 14 commercial banks only four have the national importance. The main characteristic of those banks is the share of the state. In the near future the greatest Swedish commercial bank will become the state-own bank. The further characteristics of the banks are the highly specialized long term credit institutions as well as the insurance companies which are very active in the capital market.